Materials for the earth air pipe heat exchanger (eaphe) system as a passive ground cooling technology for hot-humid climate - Hj Mohd Ariffin, Noor Aziah; Sanusi, Aliyah Nur Zafirah; Mohd Noor, Aminuddin (2014)
The implementation of the earth-air pipe heat exchanger (EAPHE) system as a passive cooling technology for both residential and commercial buildings in the hot humid climate of Malaysia is relatively new. To date this technology has not been implemented in Malaysia, although it is proven in many studies particularly in drier climates, that it has the potential to reduce energy consumption for passive cooling. Studies by local researchers on EAPHE are also limited as a passive cooling system for the country. Thinner on the ground are the potentials of the appropriate pipe materials for the EAPHE system. The study investigated the most appropriate pipe materials that will predict the optimum air temperature reduction through computer simulation studies for achieving thermal comfort. The study utilizes the EnergyPlus environmental simulation program to investigate the performances of three pipe materials system: single pipe material, hybrid pipes and insulated hybrid pipes system. Through an exhaustive enumeration process the study found that the insulated hybrid pipes system gave the best temperature reduction indicating promising cooling and energy savings potentials.